Analysis of Subsidized Diesel Quota Allocation for Ferry Boats and the Effectiveness of its Use - Aryawan, I Ketut Gede; Nofrisel, Nofrisel; Handayani, Sri (Dinasti Publisher, 2024)
Abstract: Subsidizing fuel oil (BBM), mainly diesel fuel, has become a strategic policy of the Indonesian government to support the transportation sector, including ferries. Subsidies are designed to maintain price stability and support efficient operations. The increase in the realization of fuel subsidies every year shows challenges in its management and allocation. This study aims to analyze the effectiveness and efficiency of the allocation of subsidized diesel quotas on PT ASDP Indonesia Ferry (Persero) crossing vessels in the Merak-Bakauheni crossing, as well as accountability for use. This research uses a qualitative method with a descriptive approach, involving 11 key informants with direct experience in monitoring the use of subsidized diesel. Data were collected through in-depth interviews, observation, and analysis of relevant documents. The results showed that the preparation of the subsidized diesel quota allocation has been running effectively, and the provisions set by BPH Migas carry out the distribution of subsidies. Some aspects require improvement, especially monitoring and accountability, to ensure the subsidy is used optimally. Although the allocation and distribution system of diesel fuel subsidies for PT ASDP Indonesia Ferry (Persero) crossing vessels has been quite effective, monitoring and reporting mechanisms are needed to ensure the subsidies are used optimally. Keyword: Quota, Subsidies, Diesel, Ferry Ships, Effectiveness.Subsidizing fuel oil (BBM), mainly diesel fuel, has become a strategic policy of the Indonesian government to support the transportation sector, including ferries. Subsidies are designed to maintain price stability and support efficient operations. The increase in the realization of fuel subsidies every year shows challenges in its management and allocation. This study aims to analyze the effectiveness and efficiency of the allocation of subsidized diesel quotas on PT ASDP Indonesia Ferry (Persero) crossing vessels in the Merak-Bakauheni crossing, as well as accountability for use. This research uses a qualitative method with a descriptive approach, involving 11 key informants with direct experience in monitoring the use of subsidized diesel. Data were collected through in-depth interviews, observation, and analysis of relevant documents. The results showed that the preparation of the subsidized diesel quota allocation has been running effectively, and the provisions set by BPH Migas carry out the distribution of subsidies. Some aspects require improvement, especially monitoring and accountability, to ensure the subsidy is used optimally. Although the allocation and distribution system of diesel fuel subsidies for PT ASDP Indonesia Ferry (Persero) crossing vessels has been quite effective, monitoring and reporting mechanisms are needed to ensure the subsidies are used optimally.